Food Hygiene Knowledge and Practice among South Indian Women - Mahadeva; Manasa P; Melby Elizabath; Nancy Ruby; Priya Joy; Hezil Reema Barboza (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Food is essential for the existence of all living organisms. The main purpose of food hygiene isto prepare and provide safe hygienic food and consequently contribute to a healthy family. Lack of adequatefood hygiene can lead to a number of food-borne diseases and death.Methods: A descriptive study design was adopted in order to assess the level of knowledge and practiceamong women regarding food hygiene. The tool used for this study was structured knowledge questionnaireand self-reported practice checklist. The content validity of the tool was established in consultation with 7experts. The reliability of the knowledge questionnaire was tested by split-half method and self-reportedpractice checklist by Cronbach’s Alpha. The reliability of the knowledge questionnaire was 0.8 and thepractice checklist was 0.9. Both the tool was found statistically significant. Data collected from the 132women were analyzed by descriptive and inferential statistics using SPSS.Conclusion: The results revealed that majority of the women (80.4%) belong to age group of 20-30 years.There was a positive correlation found between food hygiene knowledge and practice. Majority of thewomen had good knowledge (77.3%) and had good practice (70.3%) towards food hygiene.